2020
DOI: 10.4187/respcare.07444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Interfaces on FIO2and CO2Rebreathing During Noninvasive Ventilation

Abstract: BACKGROUND: Improving F IO 2 and reducing CO 2 rebreathing (V ICO 2) are the key means to improve the therapeutic efficacy of noninvasive ventilation (NIV). This study aimed to investigate the impact of interface design on F IO 2 and V ICO 2 during NIV. METHODS: A simulated lung model was established to analyze 17 different interfaces. CO 2 was injected into the outlet of the simulated lung, and the noninvasive ventilator was connected to the simulated lung to simulate the application of NIV in patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Masks were fit on volunteers as recommended without overtightening, and volunteers did not perceive a leak nor did it impact ventilator synchrony. Others have reported that interface’s dead space and amount of leakage impacts volume of inspired carbon dioxide ( V ICO2 ) [ 13 ]. In our study, the differences in dead space may have affect CO 2 rebreathing clearance as observed in Figure 3 , since median F ICO2 was higher for the full-face masks.…”
Section: Discussionmentioning
confidence: 99%
“…Masks were fit on volunteers as recommended without overtightening, and volunteers did not perceive a leak nor did it impact ventilator synchrony. Others have reported that interface’s dead space and amount of leakage impacts volume of inspired carbon dioxide ( V ICO2 ) [ 13 ]. In our study, the differences in dead space may have affect CO 2 rebreathing clearance as observed in Figure 3 , since median F ICO2 was higher for the full-face masks.…”
Section: Discussionmentioning
confidence: 99%
“…Erhöht man zusätzlich den Grundflow ("Bias-Flow"), dann verstärkt sich dieser Effekt [18]. Ferner beeinflussen die Bauart der Maske (nasal vs. Full-Face), der Maskentyp, der Totraum der Maske und die Position des Ausatemöffnung sowohl die F i O 2 als auch die F i CO 2 [19].…”
Section: Maskenunclassified
“…Users can set the corresponding compliance, resistance, and inspiratory negative pressure generated by an inspiratory muscle according to different models of lung disease. The parameters used in this study to simulate a COPD patient were adapted from previous publications (14)(15)(16), as follows: compliance 60 mL/cmH 2 O, inspiratory resistance 10 cmH 2 O/L/s, expiratory resistance 15 cmH 2 O/L/s, and maximum drop in inspiratory pressure −5 cmH 2 O. To simulate the negative pressure produced by the respiratory muscles, 5% of the respiratory cycle time was set to active inspiration, 3% was set to end-inspiratory hold, and 15% was set to return pressure to the baseline.…”
Section: Simulated Lung Model Settingmentioning
confidence: 99%